Assessment of the temperature and humidity index (THI) to facilitate the establishment of a ruminant rearing system in Bangladesh (Annals of Bangladesh Agriculture, 2023)
The objective of this study was to assess the  temperature-humidity index (THI) values in the selected regions of Bangladesh for the suitability of ruminant rearing. Data on monthly temperatures and relative humidity were collected from the Bangladesh Meteorological Department (BMD) for a 27-year time period (1995–2022). The study region’s data indicated that the hottest area was west central region and hottest month was June. In comparison, the coolest area was northwest region and coolest month was January. The northwest region had no heat stress from November to February, mild heat stress from March to May and October, as well as moderate heat stress from June to September. In the northeast region, mild heat stress occurred from March to May, October, and November, and moderate heat stress from June to September. December to February were comfortable, March, October, and November were mild heat stress, and April through September were moderate heat stress in the west central region. In the east central region, mild heat stress occurred in March to April, October, and November, and severe heat stress in May to September. In contrast to the west central region, which showed moderate heat stress during the rainy season, most other seasons showed mild heat stress. Thus, heat stress periods might vary depending on regional meteorological scenarios. Animals faced heat stress (THI > 72) or a warning signal due to a progressive increase in temperature and humidity indices over months and years of investigation. When THI levels are high, especially in July and August, livestock farmers must emphasize various herd management techniques to limit the risk of milk production and quality concerns, disease prevalence, and reproductive performance. The findings of the present investigation suggest heat stress mitigation measures for Bangladeshi ruminant farmers.Ann. Bangladesh Agric. 27 (2): 161-174